Nutrient Content and Acceptability of Milkfish Meatballs Substituted with Red Bean Purée for Stunting Prevention - Elvira Patinong; Hendrayati; Sukmawati (Fakultas Kedokteran, Universitas Papua, 2025)
Stunting remains a chronic nutritional problem and continues to pose a major public health challenge in Indonesia. Inadequate intake of protein and iron is recognized as one of the principal risk factors. The development of local food products rich in protein and iron is therefore required as an innovative strategy to support sustainable stunting prevention efforts. This study aimed to determine the protein and iron content as well as the acceptability of milkfish meatballs substituted with red bean purée as an alternative for stunting prevention. A pre-experimental design was employed using four meatball formulations based on different levels of red bean purée substitution (0%, 35%, 45%, and 55%). Sensory evaluation was conducted by 30 semi-trained panelists, while protein and iron analyses were performed on the selected formulation using the Kjeldahl method and Atomic Absorption Spectrophotometry. The F1 formulation (35% red bean purée) demonstrated the highest acceptability, particularly in terms of taste and texture. Nutritional analysis showed that the F1 formulation contained 11.46 g of protein and 4.50 mg of iron per 100 g of product; the protein content exceeded the minimum requirement of the Indonesian National Standard (SNI 7266:2014), and the iron content surpassed the estimated value based on the Indonesian Food Composition Table (TKPI). Milkfish meatballs substituted with red bean purée (F1 formulation) exhibited good acceptability and relatively high nutritional value, indicating their potential as a protein- and iron-rich local food-based product for stunting prevention.